Not All Practice Is Created Equal: Longitudinal Evidence From Over 40,000 Chess Players - Southwick, Daniel A.; Harwell, Kyle W.; Wright, Garrett; Olsen, Joseph A.; Ogles, Benjamin M. (Psychological Science, 2026)
In recent years, several scholars have argued that the influence of deliberate practice on expertise has been overstated. Others have contended that these critiques conflate deliberate practice with less effective forms of training. We analyzed a large, longitudinal cohort of Chess.com players ( N = 44,213) using objective, time-stamped measures of both practice activity and performance. We tested whether deliberate practice-aligned activities predict greater rating improvement than playing games. Multilevel models revealed that, despite more than 90% of player time being spent on games, deliberate practice was substantially more efficient for learning. Although not all deliberate practice-aligned activities were equally effective, the category as a whole was associated with a 3.61× advantage in learning efficiency relative to gameplay ( p s < .001). These findings offer rare real-world evidence in a long-standing theoretical debate about learning efficiency. How individuals train, not just how much, fundamentally shapes the trajectory of skill development.